Criteria for limited sanity in persons who have committed criminal sexual offenses - Kozerackaya, Elena (Psychosomatic Medicine and General Practice, 2018)
The results of scientific research conducted within the framework of the doctoral thesis "Forensic psychiatric evaluation of persons who have committed sexual criminal offences." For the purpose of the study, the author analyzed 279 cases of forensic psychiatric examinations of persons who committed the sexual offence and were at the forensic psychiatric examination in Kiev Center for Forensic Psychiatric Examination during 2001-2015 (15 years). To determine the relationship between the degree of opportunities to realize their actions/manage them and expert's conclusion, from the group of compos mentis was derived a group of partially compos mentis patients; it was formed artificially, based on the national concept of "limited sanity". As a result, we have identified socio-demographical and clinical criteria for "limited compos mentis" in forensic psychiatric examinations of persons who have committed sexual offences.